Detecção e descontaminação de Mycoplasma spp. em cultivos celulares e cepas virais - Andrade, Glaucia Prado de (2024)
Mycoplasma spp. are bacteria belonging to the class Mollicutes, considered the smallest organisms capable of self-replication (0.15 – 0.3 μm) and lacking a defined cell wall. They are associated with infections in animals and humans and are frequent contaminants of cell cultures and biological products. This high frequency is because these microorganisms are resistant to most antimicrobials used in cell cultures, do not cause observable changes under the light microscope in cultures, and often go undetected by conventional tests. However, mycoplasma contamination of cell cultures can interfere with various aspects of cellular physiology and metabolism, thus affecting the results and quality of products obtained from these cultures. Therefore, the present study aimed to investigate Mycoplasma spp. contamination in cell cultures and viral strains used in the Virology Sector of the Federal University of Santa Maria and once detected, to evaluate drugs and decontamination protocols. Among 25 cell lines and primary cultures tested for Mycoplasma spp. by PCR, 16/25 (64%) were positive, and regarding viral strains, 13/13 (100%) were contaminated, including three of bovine viral diarrhea virus 1 (BVDV-1), two of BVDV-2, one of HoBi-like virus (HobiPeV), four of bovine herpesvirus 1 (BoHV-1), one of BoHV-2, BoHV-5, and bovine parainfluenza virus 3 (PI-3V). Next, Plasmocin® [P] and gentamicin [G] were tested alone or in combination for the decontamination of bovine (MDBK and CRIB), porcine (PK-15), rabbit (RK-13), and hamster (BHK-21) cell lines. These five cultures were subjected to the decontamination protocol and tested weekly for Mycoplasma spp. via PCR. Decontamination was only possible after 35 days of treatment, with the combined treatment P + G being effective in eliminating Mycoplasma spp. from three lines (PK-15, BHK-21, and RK-13) with 35 days of treatment, and in the MDBK line with 42 days. Treatment with Plasmocin® alone decontaminated the RK-13 line with 35 days of treatment, and the MDBK line with 42 days. However, treatment with gentamicin alone was only effective in decontaminating the RK-13 line after 35 days of treatment. One cell line (CRIB) could not be decontaminated even after 70 days of combined treatment with P + G. Contamination in batches of bovine fetal serum (BFS) was also investigated, with all 12 commercial batches tested negative for Mycoplasma spp. via PCR. Subsequently, the viral strain decontamination protocol was performed. This protocol involved cycles of viral amplification in cell culture, suspension centrifugation (14,000 RPM for 15 min.), filtration (0.1 or 0.22 μm), limiting dilution, and cultivation in Mycoplasma spp.-free cells in the presence of P + G. The 13 viral strains were successfully decontaminated after 1 to 4 decontamination cycles. Thus, the present study detected the frequent contamination of cell cultures and viral strains with Mycoplasma spp. and successfully performed the decontamination of these biological inputs. Keywords: contamination, cell cultures, mycoplasma, virus, decontamination.